SheepToShip LIFE: Looking for an eco-sustainable sheep supply chain. Preliminary results on GHG emission of dairy sheep farms - Arca P.; Vagnoni E.; Lunesu M.; Serra M.G.; Contini S.; Decandia M.; Molle G.; Franca A.; Stanislao Atzori A.; Duce P. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
SheepToShip LIFE is an EU project launched in 2016 to develop an intervention model for the ecoinnovation of the Sardinian sheep-dairy supply chain, able to reduce greenhouse gas (GHG) emissions by 20% over the next 10 years through improved efficiency of production systems. This work shows the preliminary results of the Life Cycle Assessment (LCA) conducted in four case study farms, characterized by different production and management systems. The environmental performances of each farm are expressed in terms of Carbon Footprint (CF) per unit of product (fat and protein corrected milk, FPCM) and unit of area (ha of utilized agricultural area, UAA), with the additional goal of identifying the main processes that contributed to the total CF (hotspots). Farms were surveyed to gather primary data for a “from cradle to farm gate” LCA study. The average CF (CO2-eq kg FPCM-1) of the four farms was equal to about 3.4 kg CO2-eq, ranging from 2.6 to 4.2. Cropland-based farms with a higher Dairy Efficiency (DE – expressed as kg FPCM kg DMI-1) showed lower values of CF, as compared with pastureland-based farms. Contrasting results were obtained when one ha of UAA was used as functional unit. Enteric CH4 emission contributed on average about 57% of total CF, representing the main environmental hotspot.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)